Dispossession and Dehumanization: A Subaltern Study of The Underground Railroad - Muneeba Sharafat; Rasib Mahmood; Sania Gul (University of Chitral Journal of Linguistics and Literature, 2024)
Black chattel slavery by Americans is an atrocious historical phenomenon engraved in the history of America. Literature is the mouthpiece of different historical events and epitomizes those events vividly. This study focuses on dispossession and dehumanization and its impact on the plight of female slaves in Colson Whitehead’s novel, The Underground Railroad. It reflects various modes of dispossession and dehumanization in the form of separation, deprivation, objectification, indoctrination, and marginalization. The main objective of this research is to explore women portrayed as subalterns via dispossession and dehumanization in The Underground Railroad and its impact on the women in the novel. The researcher employed textual analysis and close reading techniques as this study is qualitative. The researcher has applied the postcolonial and feministic essay of Gayatri Chakravorty Spivak, “Can the Subaltern Speak?” It probes the experiences of female slaves as subalterns on the Randall plantation in the South and their journey of running away to the North. Henceforth, the present study shows the long lingering effects of slavery which started from the slave trade and continue to be there on black women in the white society. The findings show that female slaves are consistently dispossessed and dehumanized in the novel which has a devastating effect on them and their society, respectively.